Irrigation Scheduling for Tropical Fruit Groves in South Florida - Kati W. Migliaccio; Yuncong Li (EDIS)
Revised! TR001, a 6-page illustrated fact sheet by Kati W. Migliaccio and Yuncong Li, describes why irrigation is needed in south Florida, and the advantages and disadvantages of various tools available for determining an optimum irrigation schedule. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2009.